Potential impacts of oxygen impurities in carbon capture and storage on microbial community composition and activity. (October 2021) - Morgan, Hayden; Large, David J.; Bateman, Keith; Hanstock, David; Gregory, Simon P.
Highlights: Microbiological experiments were carried out to investigate the behaviour of microbial communities in CO2 and N2 with 10 ppm and 100 ppm O2 H2 S production was delayed in the CO2 experiments compared to N2 experiments Higher H2 S production and biomass was seen in CO2 experiments with 100 ppm O2 compared to 10 ppm O2 Methane production was observed in some experiments Lower O2 limits on CCS could reduce the potential for microbial activity and hydrogen sulphide production Abstract: Gaseous impurities, such as O2, are expected to be present within CO2 captured for storage. This could stimulate microbial activity in a geological CO2 storage site which has the potential to lead to operational issues such as injection well blockages, corrosion and oil souring. A series of experiments were carried out to examine the effect of 10 ppm and 100 ppm O2 in an anoxic (CO2 or N2 ) atmosphere on microbial communities and microbial gas production in laboratory scale experiments. Experiments inoculated with sulphate reducing bacteria enrichments were compared to uninoculated controls. The results show that H2 S production is delayed in a CO2 atmosphere compared to the N2 atmosphere. 100 ppm O2 in CO2 resulted in a spike of H2 S production as well as greater bacterial biomass when compared to the 10 ppm O2 in CO2 atmosphere. The inoculated N2 experiments showed similar patterns in H2 S production and biomass regardless of O2 concentration. These results suggest that a concentration of O2 lower than 100 ppm in CO2 could reduce the potential for microbial growth and H2 S production in CO2 storage sites. CH4 production was observed in some microcosms subsequent to H2 S production, highlighting the potential for microbial methanogenesis in the in CCS reservoirs.